2011
DOI: 10.3746/jkfn.2011.40.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of 4 Year-old Ginseng by Enzymatic Hydrolysis Conditions

Abstract: This study investigated quality characteristics of 4 year-old ginseng by enzymatic hydrolysis conditions to increase utilization. Ginseng was ground after steaming and was each treated with hydrolase A, B, C and D. When quality characteristics by the enzymes were examined, no significant difference was observed with pH of 5.5~5.6 and the sugar content of 4.0~4.33. The crude saponin content was the highest in ginseng treated with D, followed by B, C and A. The crude saponin, the reducing sugar and the total sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The P. ginseng fruit extract used in this study was obtained through enzymatic decomposition processes such as amylase, pectinase, and cellulase. According to previous reports, this enzymatic decomposition minimizes the destruction of major components more so than hot water extraction, and it has been reported that it can increase the extraction yield of useful components [30,31]. In this study, using this P. ginseng fruit extract, we investigated the inhibitory effect of PGFE on a periodontitis model using the ligature method and induced PG-LPS, which are representative models most widely used in periodontitis research [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The P. ginseng fruit extract used in this study was obtained through enzymatic decomposition processes such as amylase, pectinase, and cellulase. According to previous reports, this enzymatic decomposition minimizes the destruction of major components more so than hot water extraction, and it has been reported that it can increase the extraction yield of useful components [30,31]. In this study, using this P. ginseng fruit extract, we investigated the inhibitory effect of PGFE on a periodontitis model using the ligature method and induced PG-LPS, which are representative models most widely used in periodontitis research [32,33].…”
Section: Discussionmentioning
confidence: 99%